Profil erithrocyte sedimentation rate sebagai implikasi penurunan immunitas lanjut usia di panti lansia UPTD Rumoh Lansia Geunaseh Sayang Banda Aceh - Hadijah, Siti; Rahmayanti, Rahmayanti; Rizki, Zuriani (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Erythrocyte sedimentation rate (ESR) is used to determine the presence of inflammation. Highlights the importance of understanding the health conditions of the elderly, including the level of inflammation which can be measured through ESR as a non-specific marker of disease progression. Elderly people with ESR values above normal indicate that they are experiencing inflammation due to decreased immune function.Objective: This research aims to determine the ESR profile of the elderly in the Regional Technical Implementation Unit (UPTD) of the Rumoh Sejahtera Geunaseh Sayang (RSGS) Nursing Home Banda Aceh City.Methods: The research design was cross secctional, the research location was in the nursing home of the Unit Pelaksana Teknis Daerah (UPTD) Rumoh Sejahtera Geunaseh Sayang (RSGS) Banda Aceh City in July – August 2024. The sample was 70 elderly people. ESR examination uses the Westergreen method.Results: ESR values above normal are more often found in men (52,2%) than women (40,4%), with the highest prevalence in the Young Old age category (62,1%).Conclusion: Elderly men more often experience ESR values above normal, indicating that elderly men are more susceptible to decreased immune system function.